Histopathologic and Histochemic study of mice infected with Giardia - E. R. Al_Alkennany, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
This research was conducted to investigate the histopathologic and histochemic changes of small intestine and hepatic tissues of mice infected with Giardia lamblia. Results illustrated variable changes of intestinel represented by blunting and shortening of villous in the mucosa associated with hyperplasia and hypertrophy of epithelium in addition to localization of different stages of parasite. In hepatic tissue lesions characterized by diffuse vacuolar degeneration in hepatocyte and bile duct epithelium, also apoptosis has been seen concomitant with presence of parasite. Histochemically infected intestine showing a strong positive reaction with both PAS and AB (pH2.5) stains denoting an increase in mucopolysaccherid . In heptocyte strong positive reaction with both PAS and best cermine Also observed.The present study suggest that infection of mice with Giardia is (firstly time reported) communicated with alteration in tissue due to biochemical changes that produced from the interaction between parasite and cellular components.